Case Report: Mucoepidermoid carcinoma of the lung, a challenging diagnosis of an unusual case - Garijo Martínez, María C.; Olivares-Hernández, Alejandro; Bellido Hernández, Lorena; Begliardo, Fernando L.; Morchón-Araujo, Daniel; Roldán Ruiz, Jonnathan; Redondo González, Juan Carlos; Posado Domínguez, Luis; Campaña Díaz, Eva; de Dios Franco, Inés María; Fonseca Sánchez, Emilio; del Barco Morillo, Edel (Frontiers in Oncology, 2026)
BackgroundLung cancer comprises several types of tumors, with the most common subtypes being adenocarcinoma and squamous cell carcinoma. Mucoepidermoid carcinoma of the lung is an extremely rare entity, whose diagnosis and treatment are challenging.Case presentationWe reported a 55-year-old woman who was diagnosed in the context of a respiratory disease with a mucoepidermoid carcinoma of the lung. The diagnosis was not easy due to the difficulty in obtaining a correct tissue sample to study. After discussing the case in a multidisciplinary tumor board, the patient underwent surgery with the exceptional diagnosis of a low-grade mucoepidermoid carcinoma of the lung. Since then, the patient has been on follow-up, with no evidence of disease.ConclusionsThere are some subtypes of lung cancer with very different behavior from the classical ones. For example, mucoepidermoid carcinomas of the lung have an exceptional survival with surgery, without needing further treatment, when they are classified as low-grade. This case report underscores the importance of an appropriate diagnosis based on the work of multidisciplinary tumor boards, even when there are difficulties in obtaining a tissue sample, to offer to the patients the best opportunities.